The impact of industry classification schemes on financial research - Christian Weiner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper investigates industry classification systems. During the last 50 years there has been a considerable discussion of problems regarding the classification of economic data by industries. From my perspective, the central point of each classification is to determine a balance between aggregation of similar firms and differentiation between industries. This paper examines the structure and content of industrial classification schemes and how they affect financial research. I use classification systems provided by the Worldscope and the Compustat database. First, this study gives a detailed description of the structure and methodology of industrial classification systems and the relevance in leading finance and accounting journals. Second, I construct a benchmark classification system to measure the performance of different systems and provide evidence that some systems a more homogeneous in terms of value drivers than others. Third, I examine how multiple valuation is influenced by industry classification and show that the results vary significantly for different systems.
Keywords: 330